A taxonomic account of Ranunculus section Batrachium (Ranunculaceae) - Wiegleb, Gerhard; Bobrov, Alexander A.; Zalewska-Gałosz, Joanna (Phytotaxa, 2017)
In a new taxonomic account of Ranunculus section Batrachium 30 species are recognized. We present a key to the species based on morphological characters of diagnostic value. Taxonomic descriptions including information on chromosome counts, geographic range and ecological preferences are provided. For all species synonyms are listed, allowing access to the relevant taxonomic and floristic literature including taxonomic databases worldwide. Information on types and type localities is provided wherever possible. Reported and confirmed hybrids are listed and assigned to their putative parental species. Infraspecific categories such as subspecies and varieties are not recognized. Unresolved taxonomic problems are discussed for each species and for the section as a whole.